Factors of satisfaction of the questing participant in the city space - Pokorna, Magdalena; Wcisło, Martyna; Warcholik, Witold (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2024)
‘Questing’ has been operating on the market for tourism services in Polish cities for two decades. The research carried out has made it possible to identify the factors influencing participant satisfaction through this method of providing access to cultural and natural heritage. Field verification has been undertaken of the presence and content of logbooks as well as a classification of the evaluations and opinions contained on the questing websites developed for Małopolska voivodeship. Comments made by tourists, visitors and residents, in the vast majority of cases positive, are mainly a result of the presence, location and form of the so‑called treasure. Questing participants also emphasised the importance of the cultural value of the area through which the route runs, the cognitive motivation to undertake this activity and the recreational walking context. The significant advice, greetings and recommendations given by those who completed the quest testifies to a sense of shared responsibility for the final quality of this innovative service. It was shown that the specificity of the comments from notebooks (logbooks), and the opinions found on the quest supervisors’ websites were different. In the former, clients are more focused on leaving a trace of their presence and contacting subsequent questing participants, rather than evaluating the quality of the quest itself, as in the case of the websites. This may provide a clue for further research on questing attractiveness and customer satisfaction factors.